The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1943-278x.2012.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Emphasis on Autonomy and Propensity for Suicidal Behavior in Younger and Older Adults

Abstract: A cognitive style marked by emphasis on autonomy has been linked to negative outcomes throughout the life span. Two preliminary studies are presented that examined factors on a measure of autonomy (Personal Style Inventory-Revised) in relation to propensity for suicidal behavior (Suicidal Behaviors Questionnaire-14; SBQ-14). Perfectionism, B = .15, SE = 0.03, p < .01, and Defensive Separation, B = .04, SE = 0.01, p £ .01, predicted SBQ-14 in younger adults. Need for Control, B = .234, SE = 0.10, p < .05, predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
(44 reference statements)
2
26
1
1
Order By: Relevance
“…Low OTE in older adults has been found to be associated with suicide (Duberstein, ; Duberstein, Conwell, & Caine, ). Although past research has not found a significant interaction between autonomy and sex predicting suicide risk (O'Riley & Fiske, ), these findings were limited because depressive symptoms were not included in the model. A high value placed on autonomy may act as a diathesis among older adults, in whom depressive symptoms are particularly likely to be associated with stressful life events of the type that threaten autonomy (e.g., illness events; Beck, ; Mazure et al., ; Morse & Robins, ).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Low OTE in older adults has been found to be associated with suicide (Duberstein, ; Duberstein, Conwell, & Caine, ). Although past research has not found a significant interaction between autonomy and sex predicting suicide risk (O'Riley & Fiske, ), these findings were limited because depressive symptoms were not included in the model. A high value placed on autonomy may act as a diathesis among older adults, in whom depressive symptoms are particularly likely to be associated with stressful life events of the type that threaten autonomy (e.g., illness events; Beck, ; Mazure et al., ; Morse & Robins, ).…”
mentioning
confidence: 85%
“…Individuals who place a higher value on autonomy may find themselves resistant to applying a diverse set of strategies to cope with age‐related declines, thereby increasing risk for suicide. Consistent with this proposition, past research has demonstrated that older adults who endorse greater need for control, as measured by a subscale of a measure of autonomy (Robins et al., ), have greater suicidal ideation (O'Riley & Fiske, ).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Previous research has found that different subfactors within the measure of value placed on autonomy (perfectionism, defensive separation, and need for control) were associated with suicidality in younger versus older adults (O'Riley & Fiske, ). Such differences by factor may also help to explain age differences in the association between autonomy and perceived burdensomeness in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, young adults aged 18 to 29 years exhibit higher rates of suicidal ideation and attempts compared to older adults (Crosby, Han, Ortega, Parks, & Gfroerer, ). In regard to autonomy, younger adults (aged 18–24 years) score higher on measures of autonomy than older adults (O'Riley & Fiske, ). The lower scores of older adults from the West Virginia community compared to younger adults on MTurk on the CES‐D might also be explained by the relatively high functioning of community‐dwelling older adults and the relatively higher levels of clinical symptoms in MTurk samples compared to traditional samples.…”
Section: Discussionmentioning
confidence: 99%